Development of short cut design method for CO removal system - Siti Kartom Kamaruddin; Wan Ramli Wan Daud; Abdul Wahab Mohamed (2007)
Hydrogen-rich reformate produced by reforming primary fuels in the fuel processor system, contains signiﬁcant amount of CO, which is the main culprit for the performance reduction in Proton Electrolyte Membrane Fuel Cell (PEMFC) performance by CO poisoning on the Platinum catalyst at anode. Thus the reformate from the fuel processor system must be puriﬁed by removing CO before being used in the PEMFC stack. The objective of the present study is to design conceptually a CO removal system consisting of a mesoporous tubular ceramic membrane (TCM) and a pressure swing adsorber (PSA) in series. The ﬁrst section of the present study describes the design of the TCM and the second section describes the design of the PSA. The designs for both units are based on new shortcut design methods developed by the authors. The effect of some important parameters such as the temperature, pressure and membrane area on the degree of separation is investigated. It is found that theoretically, the TCM-PSA system capable of reducing the CO concentration from 2000ppm to less than 10ppm